2020
DOI: 10.21203/rs.3.rs-65516/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of Heterosis Based on Parental Genetic Distance Estimated With SSR and SNP Markers in Upland Cotton (Gossypium Hirsutum L.)

Abstract: Background: Heterosis has been extensively utilized in different crops and made a significant contribution to global food security. Genetic distance (GD) is one of the valuable criteria for selecting parents in hybrid breeding. The objectives of this study were to estimate the GD between parents using both simple sequence repeat (SSR) markers and single nucleotide polymorphism (SNP) markers and to investigate the efficiency of the prediction of hybrid performance based on GD. The experiment comprised of four m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Genetic distance is a degree of genomic differences between species or populations and it is calculated by some numerical method [38][39][40][41][42][43][44][45][46][47][48]. Very recent studies confirmed genetic distance as a valuable criterion for the selection of parents that can be used in breeding activities [49,50]. Germplasm resources proposing the highest level of genetic distance must be properly conserved and utilize in future breeding programs for their improvement [29].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic distance is a degree of genomic differences between species or populations and it is calculated by some numerical method [38][39][40][41][42][43][44][45][46][47][48]. Very recent studies confirmed genetic distance as a valuable criterion for the selection of parents that can be used in breeding activities [49,50]. Germplasm resources proposing the highest level of genetic distance must be properly conserved and utilize in future breeding programs for their improvement [29].…”
Section: Discussionmentioning
confidence: 99%